HUBUNGAN KEBIASAAN SARAPAN DENGAN KONSENTRASI BELAJAR SISWA SDN 04 BAJUR LABUAPI LOMBOK BARAT - Eggi Dian Syafraini (Yayasan Pendidikan Medika Indonesia, 2023)
Background: Efforts to build and develop the potential of human resources as successors to the nation's leadership can be carried out by improving services and providing proper and good educational infrastructure, this can run effectively supported by adequate quality nutritional intake to encourage concentration levels in learning and support academic performance. maximal brain work. Therefore, this research was tested and analyzed on the relationship between breakfast habits and student learning concentration at SDN 04 Bajur Labuapi, West Lombok. Method: The type of research being conducted was an analytic observational cross-sectional study. The research subjects were students of class IV and class V of SDN 04 Bajur Labuapi West Lombok who met the inclusion criteria and were not part of the exclusion criteria. Data collection was carried out by filling out questionnaires directly by respondents using the univariate analysis technique which in this analysis only used the distribution and percentage of each variable as well as bivariate analysis which in this study was the Spearman Correlation Test. Results: Based on the results of the Spearman correlation test between breakfast habits and the learning concentration of students in class IV and class V SDN 04 Bajur Labuapi obtained a significance value of 0.038 (p <0.05) meaning that there is a significant relationship between the two variables tested. This shows that Ho rejected and H1 is accepted, that is, there is a positive and significant relationship between breakfast habits and students' learning concentration at SDN 04 Bajur Labuapi. In addition, the correlation test obtained a correlation strength (r) of 0.289 which indicates that the strength between breakfast habits and student concentration at SDN 04 Bajur Labuapi included in the category of medium correlation strength. Conclusion: From the results of this study it can be concluded that breakfast habits affect the concentration of students in class III, class IV and class V SDN 04 Bajur Labuapi (p: 0.038, r: 0.289). The reason for most of the respondents to skip breakfast was because they woke up late.